Augmented Reality for Science Learning in the 21st Century: Systematic Literature Review - Arie Wahyu Prananta; Alfan Biroli; Mohamad Afifudin (Postgraduate, University of Mataram, 2024)
The Era of Revolution 4.0 is marked by the internet and digital technology development. Era of Revolution 4.0 is believed to affect changes in science learning which can train thinking skills of the 21st century. 21st Century Learning emphasizes learning for students on internal skills using Media, Information, and Technology; Thinking, and innovation skills. Augmented Reality is a technological innovation that is currently developing and is being used in science learning by several researchers to train 21st-century skills. The research aims to examine Augmented Reality for Science Learning in abd 21: Systematic Literature Review. The review was conducted based on state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines. The results of this research explain the focus of 21st Century learning; Augmented Reality has several advantages, Utilization of Augmented Reality for 21st Century science learning. The results of this research explain that the focus of 21st Century learning is: Competency for Critical Thinking, Innovation and Creativity, Communication, and Cooperation; Augmented Reality has several advantages and disadvantages: advantages; Is more involved, Easy to use, Can be used in general in various sources, Describe simple objects, Production that doesn't consume too many lots of expenses, Simple to use; disadvantages: sensitive to changes in perspective, There are few makers, Requires a lot of memory to Utilization of Augmented Reality: Competency for Critical Thinking, Ability to think Abstractly, Ability to Think Creatively.